Comparative acoustic analysis of standard and innovative air diffusers with enhanced mixing capabilities - Joldos Titus Otniel; Danca Paul; Cernei Alexandru (E3S Web of Conferences)
This study addresses the challenge of designing a high-induction air diffuser with a complex geometry that effectively mixes and entrains more ambient air, raising concerns about potential noise increase. The research focuses on the acoustic performance of innovative 3D-printed air diffusers compared to the original air diffuser installed in the Dacia-Renault Duster vehicle. The four 3D-printed air diffusers, created using FDM (Fused Deposition Modelling), SLS (Selective Laser Sintering), DLP (Digital Light Processing), and SLA (Stereolithography), were tested to evaluate a single configuration due to concerns that the surface quality resulting from 3D printing could increase the noise produced by these diffusers. Using a professional sound level meter, acoustic measurements were conducted at the V2 (23.9 m3/h) and V3 (33.6 m3/h) flow rate settings. Results showed that the traditional air diffuser had the highest noise levels, measuring 38.2 dB at V2 and 39.6 dB at V3, which were 7.33% and 8.84% louder, respectively, than the innovative designs. Despite the DLP-printed diffuser being the quietest on V2 speed setting, the SLA-printed variant was preferred due to its superior dimensional tolerances and because the differences in noise were small.